Wi-Fi infrastructure and wireless network monitoring programs (Eurasian Journal of Engineering and Technology, 2022)
In this article analyzes programs that allow you to detect, track and control the flow of passengers at the station through a Wi-Fi device. We also studied wireless IP cameras connected to a Wi-Fi device, their types and additional features.